Supporting older adults' engagement in health-care programs and policies: Findings from a rural cognitive health study. Issue 3 (3rd July 2019) - Bacsu, Juanita; McIntosh, Thomas; Viger, Marc; Johnson, Shanthi; Jeffery, Bonnie; Novik, Nuelle
ABSTRACT: Although rural seniors are important users of health-care services, their perspectives and input remain largely absent from health programs and policies. This article explores rural seniors' perspectives to support their engagement in patient-oriented research. Guided by lay theory and cultural schema theory, participant observation, concept maps, and semi-structured interviews were conducted with 42 rural seniors in Saskatchewan, Canada. Three themes were identified: community outreach through trust and partnership-building; using flexible data collection methods such as moving to open-ended interviews rather than closed-ended surveys; and developing community-relevant dissemination strategies such as local newspaper articles, posters, and community workshops. In moving forward, collaborative research with seniors is essential to improving health programs and policies for older adults in rural communities and beyond.